EVALUATING THE IMPACT OF GREEN BANKING INITIATIVES ON SUSTAINABLE DEVELOPMENT AND FINANCIAL PERFORMANCE: A STUDY OF INDIAN COMMERCIAL BANKS - Yadav, Shilpi; Singh, Shraddha; Vaishnav, Adarsh (ShodhKosh: Journal of Visual and Performing Arts, 2024)
Green banking has emerged as a critical paradigm in the global financial landscape, linking environmental sustainability with financial performance. This study investigates how green banking initiatives affect sustainable development and financial outcomes in selected Indian commercial banks. Using a mixed-methods approach, the research analyses primary data collected from 385 respondents across urban and semi-urban regions of Chhattisgarh, alongside secondary data drawn from financial reports, RBI publications, and sustainability disclosures. Reliability and validity of the instrument were ensured through statistical tests. The findings reveal that green banking contributes positively to environmental sustainability and moderately impacts profitability and stakeholder trust. The paper concludes with practical implications for policy and strategy development in Indian banking.